Driving Deaths and Injuries Post-9/11 - Deonandan, Raywat; Backwell, Amber (Université d'Ottawa | University of Ottawa, 2011)
Objectives: In the days immediately following the terror attacks of 9/11, thousands of Americans chose to drive rather than to fly. We analyzed highway accident data to determine whether or not the number of fatalities and injuries following 9/11 differed from those in the same time period in 2000 and 2002. Methods: Motor crash data from the National Highway Traffic Safety Administration’s Fatality Analysis Reporting System were analyzed to determine the numbers and rates of fatalities and injuries nationally and in selected states for the 20 days after September 11, in each of 2000, 2001, and 2002. Results: While the fatality rate did not change appreciably, the number of less severe injuries was statistically higher in 2001 than in 2000, both nationally and in New York State. Conclusions: The fear of terror attacks may have compelled Americans to drive instead of fly. They were thus exposed to the heightened risk of injury and death posed by driving. The need for public health to manage risk perception and communication is thus heightened in an era of global fear and terrorism.
Keywords: public health; traffic; injuries; epidemiology